Strategic plan 1998-2001
This Strategic Plan of the Australian Sports Commission covers the period 1998 - 2001. It sets the broad framework within which the Commission will pursue its primary objectives and it identifies the strategies for achieving these objectives. It describes the context and environment against which these strategies have been formed.